Design of a three-dimensional hand/forearm model to apply computational fluid dynamics - Marinho,Daniel Almeida (2010)
The purpose of this study was to develop a three-dimensional digital model of a human hand and forearm to apply Computational Fluid Dynamics to propulsion analysis in swimming. Computer tomography scans of the hand and forearm of an Olympic swimmer were applied. The data were converted, using image processing techniques, into relevant coordinate input, which could be used in Computational Fluid Dynamics software. From that analysis, it was possible to verify an almost perfect agreement between the true human segment and the digital model. This technique could be used as a means to overcome the difficulties in developing a true three-dimensional model of a specific segment of the human body. Additionally, it could be used to improve the use of Computational Fluid Dynamics generally in sports and specifically in swimming studies, decreasing the gap between the experimental and the computational data.